The Connection Between ICT Development Level and The Use of Information Systems by Micro-Enterprises - Peter Sasvari; Zsuzsa Majoros (- ii, 21–24 2013 . , 2, 2013)
In the era of unstoppable IT development, the use of various information systems is an essential requirement for all enterprises. In particular, micro-enterprises are in a difficult position since they need continuous development to remain competitive with the possible help of information systems. At the same time, these enterprises that employ only a few people cannot afford to implement expensive software applications. Analysing the use of information systems among microenterprises is very important as they typically form the majority of enterprises, having a significant influence on the economic situation of each country. The present paper is aimed at analysing the use of information systems by micro-enterprises in Germany, Hungary and Slovakia. – – . () . . , .
Additional information: « - » - II , 21–24 2013 . 2 2013 ISBN 978-985-540-048-7 (. 2) http://www.gii.gomel.by/novosti/748-innovatsionnye-tekhnologii-v-ekonomicheskom-i-biznes-obrazovanii
Keywords: M13; M15; 330; ICT; Hungary; Slovakia; Germany; Business Information Systems; micro-enterprises